Illness Acceptance as the Measure of the Quality of Life in Moderate Psoriasis - Jankowiak B; Kowalewska B; Krajewska- Kułak E; Milewski R; Turosz MA (Dove Medical Press, 2021)
Barbara Jankowiak,1 Beata Kowalewska,1 Elżbieta Krajewska- Kułak,1 Rafał Milewski,2 Maria Anna Turosz3 1Department of Integrated Medical Care, Medical University of Bialystok, Bialystok, Poland; 2Faculty of Health Sciences Medical University of Bialystok, Bialystok, Poland; 3Faculty of Physical Education and Health Jozef Pilsudski University of Physical Education in Warsaw, Faculty in Biala Podlaska, Biala Podlaska, PolandCorrespondence: Barbara JankowiakDepartment of Integrated Medical Care, Medical University of Bialystok, 7A MC Skłodowskiej Str, Bialystok, 15-096, PolandTel +48 85 748 55 28Email barbara.jankowiak@umb.edu.plIntroduction: Psoriasis is a chronic disease with intermittent flares and remissions. Each individual perceives the disease, its somatic effects, resultant dysfunction and related problems differently. This attitude is primarily determined by one's characterological traits and type of illness. A primary response to the diagnosis can be denial, underestimation, acceptance or overestimation of the disease. The aim of the study was to analyze the level of illness acceptance and its effect on the quality of life in moderate psoriasis depending on sociodemographic and clinical characteristics of the patients.Materials and Methods: The study included 186 patients with plaque psoriasis with Psoriasis Area Severity Index (PASI) scores ≤ 10. The inclusion criteria of the study were duration of psoriasis > 2 years, age ≥ 18 years, and lack of other somatic or mental disorders during three months preceding the study. The study participants completed the Acceptance of Illness Scale (AIS), Dermatology Life Quality Index (DLQI) as well as an original survey containing questions about their sociodemographic characteristics and information about their disease.Results: Mean AIS score for the study group was 24.3 pts. Patients older than 40 years presented with lower levels of illness acceptance than younger persons (p = 0.0311). Also, patients' sex and duration of psoriasis significantly affected the acceptance of the illness, with lower AIS scores found in women (p = 0.0092) and persons with a longer history of the disease (p = 0.0362). Mean DLQI score for the study group was 13.3 pts. A lower level of illness acceptance turned out to exert an unfavorable effect on the quality of life (QOL) in psoriasis (p = 0.0015; R = − 0.33).Conclusion: In this study, patients with psoriasis presented with a moderate level of the illness acceptance, and a significant correlation was found between this parameter and QOL.Keywords: illness acceptance, psoriasis, psychodermatology, quality of life